De la Precatio Terrae y la Precatio omnium herbarum a un texto inacabado: las precationes herbarum de un recetario médico tardoantiguo - Ferraces Rodríguez, Arsenio (Acta Classica Universitatis Scientiarum Debreceniensis, 2021)
The Curae herbarum is a late antique medical recipe book made up of 64 chapters; it is mostly based on a Latin translation of the De materia medica by Dioscorides. Chapters 1–32 always end with a precatio to the plant so that it ‘comes with all its healing powers’. The article argues for an erudite origin for the precationes of the Curae herbarum, which borrow epithets, phraseology, and verbs of entreaty from the Precatio Terrae and the Precatio omnium herbarum. Moreover, the study of internal references in the precationes demonstrates that they were written with the intention of being placed before the medical recipes, but, for unknown reasons, were instead copied at the end of the chapters without ever occupying the place they were intended for.